2003
DOI: 10.1161/01.cir.0000068375.40887.fa
|View full text |Cite
|
Sign up to set email alerts
|

Region- and Type-Specific Induction of Matrix Metalloproteinases in Post–Myocardial Infarction Remodeling

Abstract: Background-Induction of matrix metalloproteinases (MMPs) contributes to adverse remodeling after myocardial infarction (MI). Whether a region-and type-specific distribution of MMPs occurs within the post-MI myocardium remained unknown. Methods and Results-Ten sheep were instrumented with a sonomicrometry array to measure dimensions in 7 distinct regions corresponding to the remote, transition, and MI regions. Eight sheep served as reference controls. The relative abundance of representative MMP types and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
219
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(246 citation statements)
references
References 33 publications
19
219
2
6
Order By: Relevance
“…Several enzymes are capable of mediating this cleavage, and several, including MMP-8, MMP-13, and MMP-14, are expressed after myocardial infarction. 8,27,28 Thus, Col1a1 r/r mice constitute a powerful tool for elucidating the role of collagen degradation during infarct healing, and their use circumvents compensation or redundancy among collagen-degrading enzymes. In addition, collagenases can have targets other than type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Several enzymes are capable of mediating this cleavage, and several, including MMP-8, MMP-13, and MMP-14, are expressed after myocardial infarction. 8,27,28 Thus, Col1a1 r/r mice constitute a powerful tool for elucidating the role of collagen degradation during infarct healing, and their use circumvents compensation or redundancy among collagen-degrading enzymes. In addition, collagenases can have targets other than type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…The study also demonstrated that MMP-9, which increased in the myocardium, was leukocyte-derived. From a large animal study (24), AMI was induced in sheep, and the tissue levels of MMPs and TIMPs were studied at eight weeks. Wilson et al (24) found that the region-and type-specific changes in MMPs occurred after MI.…”
Section: Myocardial Infarction and Mmpsmentioning
confidence: 99%
“…Studies of mice with a targeted deletion of mmp9 clearly implicate this factor in not only left ventricular dilation but also in inhibition of neo-angiogenesis postinfarct (1,10,15,22,23,38). Other studies suggest MMP13 may also be important in late progression of remodeling (46).…”
mentioning
confidence: 99%